Impact on Creatinine Clearance in Obstructive Kidney After Percutaneous Nephrostomy (Medical Forum Monthly, 2024)
at People’s Medical College Hospital Nawabshah. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Urological Department and Urology OPD of People’s Medical College Hospital Nawabshah from January 2017 to August 2018 Materials and Methods: All the patients were admitted through Emergency/urological Outpatient Department of the Hospital. History, examination and required investigations were done. PCN was done in all patients and outcome was assessed according to the follow up visits. Results: A total of 70 patients were included in this study. There were 40(57.14%) males and 30(42.86%) females. Age ranged from 12 to 70 years. 15 (21.42%) patients aged from 12 to 15 years. 20 (28.57%) patients were of 17 to 30 years and 35(50%) patients age was from 31 to 70 as is shown in table 1 below. The average age was 35 to 40 years. In 71.42% patients, Pre PCN creatinine was 2-3.5mg/dl but post PCN was 0.8-1.2mg/dl. Pre PCN clearance was 30-35ml/m in 77.14%. Conclusion: The conclusion is that PCN is the best procedure to revive the function of kidney.